2020
DOI: 10.1177/0194599820925454
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain in Infants With Pierre Robin Sequence in the First Year of Life

Abstract: Objective To compare growth trends among infants with Pierre Robin sequence (PRS) to normal World Health Organization (WHO) growth standards. Study Design Case series with chart review. Subjects and Methods Twenty-four infants with syndromic and nonsyndromic PRS (54% male) treated at an urban academic medical center between 2009 and 2017 were included. Infants with symptomatic hypoventilation underwent mandibular distraction osteogenesis (71%). Weights were recorded at roughly 1- to 3-month intervals from birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Recently, in another review case series, the weight of 24 infants with isolated RS and syndromic RS was compared with the normal controls. In this review study, investigators reported that newborns with and without PRS had similar birth weights, but the growth rate of infants with PRS lagged behind the normal controls even if addressed at an early stage [34].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, in another review case series, the weight of 24 infants with isolated RS and syndromic RS was compared with the normal controls. In this review study, investigators reported that newborns with and without PRS had similar birth weights, but the growth rate of infants with PRS lagged behind the normal controls even if addressed at an early stage [34].…”
Section: Discussionmentioning
confidence: 94%
“…A slower growth rate compared to WHO norms was also observed in 24 RS infants predominantly treated with mandibular distraction osteogenesis. These infants showed a marked decrease in growth rate in the first 6 months after birth, with Z-scores at 3 and 5 months of age being − 2.19 and − 1.64, respectively [ 17 ]. After a subsequent period of accelerated growth in most infants, boys had caught up with their unaffected peers by 12 months of age, while girls continued to show a weight below WHO norms [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These infants showed a marked decrease in growth rate in the first 6 months after birth, with Z-scores at 3 and 5 months of age being − 2.19 and − 1.64, respectively [ 17 ]. After a subsequent period of accelerated growth in most infants, boys had caught up with their unaffected peers by 12 months of age, while girls continued to show a weight below WHO norms [ 17 ]. In a Dutch study on 69 infants with RS, growth in the first 2 years was significantly lower than in patients with isolated cleft palate [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group calculated standard deviation (Z‐)scores for weight throughout the first year of life in 24 infants with RS, with 17 being treated by MDO. Their Z‐scores changed from + 0.1 and −0.8, respectively, in girls and boys at birth to a nadir of −1.6 at 5 months in girls, and −2.1 at 3 months in boys, translating in a mean weight deficit compared to the World Health Organisation standard of 1.7 and 1.4 kg at these time points 61 . Catch‐up growth following MDO onset has also been reported in a retrospective analysis from Yale, in parallel to an increase in the proportion of infants being fully orally fed from 50% pre‐operatively to 73% at 6 months after surgery 62 …”
Section: Surgical Interventionsmentioning
confidence: 97%